Analysis of GRACE range-rate residuals with focus on KBR instrument system noise - Goswami, Sujata; Devaraju, Balaji; Weigelt, Matthias; Mayer-Gürr, Torsten (Advances in space research, 2018)
We investigate the post-fit range-rate residuals after the gravity field parameter estimation from the inter-satellite ranging data of the gravity recovery and climate experiment (grace) satellite mission. Of particular interest is the high-frequency spectrum (f> 20 mhz) which is dominated by the microwave ranging system noise. Such analysis is carried out to understand the yet unsolved discrepancy between the predicted baseline errors and the observed ones. The analysis consists of two parts. First, we present the effects in the signal-to-noise ratio (snrs) of the k-band ranging system. The snrs are also affected by the moon intrusions into the star cameras’ field of view and magnetic torquer rod currents in addition to the effects presented by Harvey et al. (2016). Second, we analyze the range-rate residuals to study the effects of the kbr system noise. The range-rate residuals are dominated by the non-stationary errors in the high-frequency observations. These high-frequency errors in the range-rate residuals are found to be dependent on the temperature and effects of sun intrusion into the star cameras’ field of view reflected in the snrs of the k-band phase observations.